2013
DOI: 10.1159/000357602
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Therapy - an Expert Panel Update of the 2002 Consensus Guidelines

Abstract: Fasting for medical purpose (fasting therapy) has a long tradition in Europe and is established as a defined therapeutic approach in specialized fasting hospitals or within clinical departments for integrative medicine. In 2002, the first guidelines for fasting therapy were published following an expert consensus conference; here we present a revised update elaborated by an expert panel. Historical aspects and definitions, indications, methods, forms, and accompanying procedures of fasting as well as safety an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
98
0
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 26 publications
(30 reference statements)
1
98
0
18
Order By: Relevance
“…All subjects fasted according to the fasting programme of the BWC which is documented in the guidelines of the fasting therapy (5) . They stayed under daily supervision of nurses and physicians specialised in fasting therapy.…”
Section: Fasting Interventionmentioning
confidence: 99%
“…All subjects fasted according to the fasting programme of the BWC which is documented in the guidelines of the fasting therapy (5) . They stayed under daily supervision of nurses and physicians specialised in fasting therapy.…”
Section: Fasting Interventionmentioning
confidence: 99%
“…Therapeutic fasting is claimed to be generally safe and well tolerated, though there are some contraindications. Rather surprisingly, psychotic disorders have been considered among indications presenting a risk (Wilhelmi de Toledo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We know, however, that metabolic disturbances are common in both drug naive and treatment experienced patients with schizophrenia (Britvic et al, 2013;Grover et al, 2012) and that fasting allegedly may improve these disturbances (Shariatpanahi et al, 2012). Yet, according to the latest consensus guidelines for fasting therapy, psychotic disorders are considered an 'indication presenting a risk' (Wilhelmi de Toledo et al, 2013), while as noted by Fond et al (2013), one cannot determine from the available literature the reason why fasting is risky in psychosis. Anecdotally, we are aware of patients with chronic schizophrenia who observe Ramadan fasting year after year with generally no problems.…”
Section: Introductionmentioning
confidence: 99%
“…A multimodal, medical supervised fasting regimen, including medical, psychosocial and cognitive dimensions called "Buchinger Fasting" has a long tradition in Europe and is established as a de ned therapeutic approach in specialized fasting hospitals [5].This multimodal type of fasting intervention has been shown to be effective in a number of conditions that could potentially be relevant to people with type 1 diabetes, such as depressive disorders, exhaustion / fatigue, the metabolic syndrome including type 2 diabetes and autoimmune diseases such as rheumatoid arthritis [6], [7], [8]. A guideline on the method has been published [5]. The evaluation of 1422 subjects following a Buchinger fasting lasting 21 days showed that this intervention is safe and well tolerated in people without type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%